Recent Publications (Quarterly Journal of Economics, 1950)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 64, Issue 2, May 1950, Pages 328–331, https://doi.org/10.1093/qje/64.2.328 Published: 01 May 1950